2023
DOI: 10.1002/slct.202300845
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Oxidative Cross‐Dehydrogenative Coupling of Alkenes with Thiophenols

Abstract: A novel transition‐metal‐free regioselective allylic C−H thiolation of alkenes has been achieved by cross‐dehydrogenative coupling strategy. The present protocol realizes efficient and highly regio‐ and stereo‐selective functionalization of allylic C−H bonds under metal‐free conditions, leading to a series of allylic thioethers in good to excellent yields. Moreover, this work features mild reaction conditions, high step‐ and atom‐economy and good functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…Moreover, Song's group revealed that the transition metal tungsten catalytic system could realize the oxidative dehydrogenative coupling of anilines for the synthesis of azoaromatics and azoxyaromatics [34]. Herein, considering the significance of organosulfur molecules and our continuous interest in aerobic cross-dehydrogenative coupling reactions for the construction of organosulfur compounds [35,36], we disclosed a tungsten-catalyzed aerobic oxidative cross-dehydrogenative coupling of thiols and phosphonates or indoles for the facile synthesis of organosulfur derivatives after exerting tremendous efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Song's group revealed that the transition metal tungsten catalytic system could realize the oxidative dehydrogenative coupling of anilines for the synthesis of azoaromatics and azoxyaromatics [34]. Herein, considering the significance of organosulfur molecules and our continuous interest in aerobic cross-dehydrogenative coupling reactions for the construction of organosulfur compounds [35,36], we disclosed a tungsten-catalyzed aerobic oxidative cross-dehydrogenative coupling of thiols and phosphonates or indoles for the facile synthesis of organosulfur derivatives after exerting tremendous efforts.…”
Section: Introductionmentioning
confidence: 99%